2014
DOI: 10.4067/s0034-98872014000600009
|View full text |Cite
|
Sign up to set email alerts
|

Compromiso multisistémico en apnea obstructiva del sueño

Abstract: . El diagnóstico se establece mediante la demostración de eventos obstructivos mediante polisomnografía o la poligrafía respiratoria, la que demuestra el índice de apnea e hipoapnea (AHI), indicador de severidad de SAOS. Un AHI < 5 es normal; leve, 5 a 10; moderado, 15 a 30 y severo > 30 [1][2][3] . La terapia se basa en tratamiento conservador e incluyen la pérdida de peso, higiene del sueño, corrección con terapia postural y manejo de factores como la congestión nasal. En aquellos pacientes con SAOS moderado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 48 publications
0
7
0
3
Order By: Relevance
“…Disturbed sleep and nocturnal altered breathing are related to disturbances of glucose metabolism. Many studies have explored the role of these factors on the variability of fasting glycemia [17] [18]. They have revealed that the respiratory and sleep disturbances that are seen due to a variety of factors have a very direct influencing effect on the glycemic control of a patient.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbed sleep and nocturnal altered breathing are related to disturbances of glucose metabolism. Many studies have explored the role of these factors on the variability of fasting glycemia [17] [18]. They have revealed that the respiratory and sleep disturbances that are seen due to a variety of factors have a very direct influencing effect on the glycemic control of a patient.…”
Section: Discussionmentioning
confidence: 99%
“…В последние годы открыты механизмы связи СОАС с нейрокогнитивной, эндокринной, сердечно-сосудистой системами и метаболическими нарушениями. Доказано, что СОАС не просто усугубляет течение сердечной недостаточности (СН), способствует нарушениям ритма сердца, являясь предиктором возникновения и рецидива фибрилляции предсердий, но и повышает риск общей смертности вне зависимости от причин [27,28].…”
Section: влияние гэрб на течение ибсunclassified
“…It is a common sleep disorder characterized by repetitive upper airway collapse with apnea/hypopnea and recurrent hypoxia during sleep, which results in fragmented sleep and intermittent drops in arterial blood oxygen saturation (hypoxemia) (2). The potential consequences of OSA involve multiple systems including cardiovascular, endocrine, and respiratory and neurocognitive dysfunction.…”
Section: Contextmentioning
confidence: 99%